The Expert System For Diagnosing Lovebird Diseases By Algorithm Certainty Factor - Baggash Adytia Pratama; Dewi Suranti; Lena Elfianty (Penerbit Jurnal Indonesia, 2021)
This study aims to diagnose disease in lovebirds using the Certainty Factor Algorithm. Lovebird is a type of bird that is much favored by the public. Lovebird is known as a race bird that has a unique song. However, the lack of knowledge of treatment for lovebirds if they are sick. Therefore, an expert system was designed to diagnose lovebird disease with the Certainty Factor method. This expert system is expected to be used by bird lovers. Love Bird. This expert system is designed using the PHP programming language and MySQL database. The expert system created can make it easy for users to consult about lovebird diseases online. The research method used by the author is the waterfall method. The application of the Certainty Factor method in this Lovebird expert system can be used in determining Lovebird disease. So that this expert system can be used as a tool in diagnosing disease in Lovebird. The MySQL database can accommodate information and data from users who consult with this expert system. Based on the results of the tests that have been carried out, the expert system for diagnosing Lovebird disease can provide convenience for users to consult about Lovebird disease.